Protecting-Group-Free Synthesis of GB1107: An Orally Active Galectin-3 Antagonist - St-Gelais, Jacob; Giguère, Denis (Synthesis, 2021)
Small-molecule galectin inhibitors are useful research tools that could also be used as potential drug candidates. In that context, GB1107, a monosaccharidic galectin inhibitor, was shown to be an orally active galectin-3 antagonist that inhibits lung adenocarcinoma growth. Herein, a protecting-group-free synthesis of GB1107, along with other analogues is described. Starting from inexpensive levoglucosan, a Payne rearrangement/azidation process was used as key step. Finally, the use of a log P determination method based on 19F NMR spectroscopy was explored to assess the lipophilicity of galectin inhibitors.
Keywords: synthetic inhibitors; galectins; GB1107; TD139; lipophilicity